Lens-specific expression and developmental regulation of the bacterial chloramphenicol acetyltransferase gene driven by the murine alpha A-crystallin promoter in transgenic mice. - Overbeek, P A (1985)
Two lines of transgenic mice with one to two copies of a DNA fragment containing nucleotides -364 to +45 of the murine alpha A-crystallin gene linked to the bacterial chloramphenicol acetyltransferase (CAT) gene expressed the CAT gene only in their eye lenses. Both CAT activity and alpha A-crystallin were first detected in eyes at approximately 12.5 days of embryonic development, suggesting that the alpha A-CAT fusion gene and the endogenous alpha A-crystallin gene are co-regulated during lens development in the transgenic mice. These experiments show that the murine alpha A-crystallin gene contains a short, cis-acting, tissue-specific regulatory sequence at its 5' end that can target the expression of the bacterial CAT gene, and probably foreign eukaryotic genes, specifically to the ocular lens.